Analysis of the Factors Affecting the Amount of Pension Salary at the Public Works, Spatial Planning, and Construction Service in the City of Bandung - Aritonang, Marta Juni Mulia; Adji, Widwi Handari (Pascasarjana STIE Miftahul Huda, 2025)
This study examines the factors influencing the amount of retirement salary received by employees at the Department of Human Settlements, Construction, and Spatial Planning of Bandung City. The three main factors analyzed are length of service, education level, and the last rank or position held. The results indicate that the last rank or position has the greatest impact on the retirement salary, followed by education and length of service. The higher the rank and education level, as well as the longer the length of service, the greater the retirement salary received. Beyond the numerical data, this study also highlights the experiences of retirees who feel that their pension significantly supports their lives after retirement. The retirement salary serves as a form of appreciation for their dedication and provides a sense of security in old age. This research hopes that the pension system will continue to be improved to become more equitable and beneficial for all employees.